Food Cost Variance Analysis: Case Study of Novotel Karawang - Zikir Zibran Firdaus; Ahmad Nurkhin (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study researched the food cost variance at Novotel Karawang from July to December 2024 in order to evaluate the effectiveness of food cost management. The study centered on the five top-selling menus by analyzing the actual costs in comparison with standard costs, with a specific focus on the price, quantity, also both joint price and quantity variations. The methodology chosen was quantitative descriptive, leveraging secondary data from the hotel's finance and accounting department. The results showed that actual costs were consistently higher than standard costs, with four out of the five menus showing unfavorable overall variances. Unfavorable prices variations caused on by fluctuating market prices and unfavorable quantity variances caused on by inefficient raw material use were the main causes. Nonetheless, one menu showed a positive overall variance, indicating the possibility of efficient cost management. The research results suggest that in order to reduce cost inefficiencies, Novotel Karawang's management ought to prioritize continuous supervision of purchasing strategies and operational processes top priority. A useful methodology for locating and resolving food cost variations in the hospitality sector is offered by this study.